Fink's integrated course design and taxonomy: The impact of their use in a “Basics of Dental Anatomy” course (2020)
Objective: This study aimed to assess whether the adjustment of Fink's Model of Integrated Course Design (ICD) with his Taxonomy of Significant Learning (hereinafter referred to as “ICD/SL”) affected the academic performance of students at Universidad El Bosque in the “Basics of Dental Anatomy” course. Design: For this purpose, 3 academic groups were selected: 2018/1 (55 students), 2018/2 (79 students), and 2019/1 (57 students). The control group, 2018/1, was taught without ICD/SL; the 2 treatment groups, 2018/2 and 2019/1, was taught with ICD/SL, which applied revised learning goals based on Fink's Taxonomy and new teaching and evaluation activities. The assessment of academic performance was based on a Likert scale to position student results in each grade score report. Statistical analysis was performed through the Kruskal-Wallis test and P-value through the Mann-Whitney U test and Fisher exact test. Results: The results indicated that the treatment groups evidenced better academic performance in the summative assessment of the partial and final grades. In the treatment groups, 64% to 97% of students were in the High to Excellent segment; in comparison, this percentage in the control group was 44% to 65%. The course's rate of failure dropped from 10.9% in 2018/1 to only 1.7% in 2019/1. All the differences between the treatment and control groups were statistically significant (P < 0.0001). Conclusion: The use of ICD/SL improved the academic performance of students. © 2020 American Dental Education Association